Architecture and verification of enhanced deterministic networking oriented large-scale - Jun XU; Aihua LIU; Guoquan KONG; Quan XIONG (Dianxin kexue)
Comparison to the traditional “best-effort” QoS of IP-based network, deterministic networking had provided guaranteed QoS capabilities catering the requirements of differentiated increasing IP-based services.In the local Ethernet network and limited domain IP network, IEEE and IETF had approved the time-sensitive networking and deterministic working groups, which had published series standards.At present, the large-scale deterministic networking research has been carried out in the industry.There has being a consensus that the deterministic networking technology needs to be enhanced, and a new enhanced deterministic networking architecture needs to be developed.A three-dimension enhanced networking architecture was proposed, and the prototype devices verification based the architecture were provided.The results of verification show that it can meet the large-scale deterministic requirements with the well compatibilites for existed IP network.